Cognitive functioning during long-term tamoxifen treatment in postmenopausal women with breast cancer. Issue 1 (January 2015) - Boele, Florien W.; Schilder, Christina M.T.; de Roode, Mari-Lou; Deijen, Jan Berend; Schagen, Sanne B.
Abstract: Objective: Endocrine therapy is widely used—often for many years—in women with breast cancer. Yet little is known about cognitive functioning after long-term use of tamoxifen. We examine cognitive sequelae, approximately 3 years after diagnosis, in postmenopausal women with breast cancer who were treated with adjuvant tamoxifen. Methods: Data from participants who underwent surgical operation with or without radiotherapy, participants who received adjuvant tamoxifen, and healthy controls were collected. Neuropsychological tests were administered, and participants completed questionnaires on health-related quality of life (Quality of Life Questionnaire Core 30 and Breast Cancer–Specific Quality-of-Life Questionnaire), menopausal symptoms (Functional Assessment of Cancer Therapy—Breast endocrine symptom subscale), and anxiety and depression (Hopkins Symptom Checklist). Results: In total, 107 women participated (adjuvant tamoxifen group, n = 20; surgical operation/radiotherapy group, n = 43; healthy control group, n = 44). Women in the adjuvant tamoxifen group had received tamoxifen for a mean (SD) of 31.5 (18.6) months (range, 15-79 mo) and performed worse on verbal memory than the surgical operation/radiotherapy group ( P < 0.05) and the healthy control group ( P < 0.05). Participants in the adjuvant tamoxifen group performed worse on measures of fluency than healthy controls ( P < 0.05). Furthermore, women in the adjuvant tamoxifen group reported worse cognitive functioning ( P < 0.05) than women in the surgical operation/radiotherapy group or the healthy control group. Conclusions: Our results provide insights into cognitive functioning in women who receive long-term adjuvant tamoxifen treatment. By adding the surgical operation/radiotherapy group, we could control for the mental and physical influences of the diagnosis and treatment of breast cancer. Cognitive domains that rely on verbal abilities (verbal memory and fluency) seem to be at risk for deterioration after treatment with tamoxifen.